2014
DOI: 10.4209/aaqr.2013.03.0074
|View full text |Cite
|
Sign up to set email alerts
|

Road Dust Emission Sources and Assessment of Street Washing Effect

Abstract: Although previous studies report on the effect of street washing on ambient particulate matter levels, there is a lack of studies investigating the results of street washing on the emission strength of road dust. A sampling campaign was conducted in Madrid urban area during July 2009 where road dust samples were collected in two sites, namely Reference site (where the road surface was not washed) and Pelayo site (where street washing was performed daily during night). Following the chemical characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Water spray (from sprinkler on road or atop a tall building) to simulate natural types of precipitation has been proposed as an important abatement strategy to facilitate the reduction of ambient PM concentrations (including trace elements) in urban China (Liu et al, 2014;Yu, 2014). However, several field measurements revealed that water spray activities did not influence the PM mass levels (e.g., Karanasiou et al, 2012;Karanasiou, 2014). Taking advantage of our simultaneous and hourly record of the precipitation amount (up to 37 mm) and the elemental concentration, here we evaluate the effects of precipitation on the mitigation of PM 2.5 trace elements.…”
Section: Precipitation Effectmentioning
confidence: 99%
“…Water spray (from sprinkler on road or atop a tall building) to simulate natural types of precipitation has been proposed as an important abatement strategy to facilitate the reduction of ambient PM concentrations (including trace elements) in urban China (Liu et al, 2014;Yu, 2014). However, several field measurements revealed that water spray activities did not influence the PM mass levels (e.g., Karanasiou et al, 2012;Karanasiou, 2014). Taking advantage of our simultaneous and hourly record of the precipitation amount (up to 37 mm) and the elemental concentration, here we evaluate the effects of precipitation on the mitigation of PM 2.5 trace elements.…”
Section: Precipitation Effectmentioning
confidence: 99%
“…Typically, airborne particles are collected using specialised samplers with filters. Some studies in the urban environment have determined sources of road-deposited sediment (RDS) which is itself a major source of PM10 and PM2.5 and an important contributor to the fine-grained sediment load of urban rivers (Owens et al, 2011;Karanasiou et al, 2014).…”
Section: Human Health Applications: Fingerprinting Airborne Particlesmentioning
confidence: 99%
“…The major sources of dust pollution include suspension of soil, agriculture related activities, road dust, vehicular exhaust, power plants, construction activities, brick kilns and cement factories etc. (Karanasiou et al, 2014;Upadhyay et al, 2015). In addition, transboundary and long range transport also contributes a significant amount of atmospheric dust in the south Asian region (Begum et al, 2011).…”
Section: Introductionmentioning
confidence: 99%